Feasibility of a documentary film on human reproductive system - Nurfadillah, Rezkiana; Panjaitan, Ruqiah Ganda Putri; Wahyuni, Eko Sri (Biosfer: Jurnal Pendidikan Biologi, 2025)
The continuous advancement of technology in the era of globalization has an inevitable impact on the educational sector, particularly in the learning process. The use of media is one of the critical components in this process. This research develops an educational medium in the form of a documentary film about the human reproductive system, based on an inventory of medicinal plants for male reproductive health in Padang Tikar Village. This documentary film is designed to support the explanation of abstract concepts related to the human reproductive system, thereby facilitating the understanding of material that cannot be directly observed. The objective of this study is to develop and assess the feasibility of an instructional medium in the form of a documentary film on the human reproductive system, based on the inventory of medicinal plants for male reproductive health in Padang Tikar Village, West Kalimantan, Indonesia. The research design employs a Research and Development (R&D) approach, limited to five stages: identifying potential and problems, data collection, product design, design validation, and design revision. The research instruments used include an interview sheet with Grade XI Biology teachers and a feasibility test sheet for validating the documentary film by five validators, consisting of three Biology teachers and two Biology Education lecturers, to assess the documentary's feasibility in terms of format, content, language, and usability. The validation analysis employs a formula based on Aiken’s V (Aiken, 1985). Results show that the documentary film achieved high validity in all aspects, with average scores of 0.84 for format, 0.85 for content, 0.93 for language, and 0.91 for usability. The overall average score was 0.87. These findings indicate that the developed documentary film is highly feasible and can be used as an effective educational medium for teaching the human reproductive system.